A CRISE HABITACIONAL E O ESTADO NA CONSTRUÇÃO DE MORADIAS NA CIDADE DO RIO DE JANEIRO (1945-50) (Revista de História Regional, 2007)
The purpose of this article is to understand the participation of the State (both Federal and Municipal) in the housing construction in face of a very dramatic housing crisis in the City of Rio de Janeiro during the period of 1945 through 1950. It presents the state investment in the construction of houses, either by financial plans or by own resources (for sale or rent). Within this perspective,we have analyzed the role of the Institutes for Pensions and Retirements Plans (IAPs- Institutos de Aposentadorias e Pensões) and the Foundation for Popular Housing (FCP - Fundação da Casa Popular) at the federal level, and the construction of houses by the Federal District Town Hall.